Infliximab in patients with inflammatory DMARDs-refractory eye disease - García-Salazar, Elmer (2013)
Experience with infliximab (monoclonal antibody with strong anti-inflammatory action) for treatment of ocular inflammatory disease secondary to rheumatic diseases and refractory to disease-modifying antirheumatic drugs (DMARDs) is described. We evaluated the cases of a 50 year-old patient with active rheumatoid arthritis (RA) and a 37 year-old patient with myeloperoxidase antineutrophil cytoplasmic vasculitis antibody (MPO ANCA) without noble organ affectation, both with bilateral scleritis and left eye corneal perforation with iris prolapse. They received infliximab 3-5 mg/kg IV at 0, 2, 6, and 8 weeks. Infliximab was effective and safe for treatment of scleritis associated to RA and MPO ANCA positive vasculitis refractory to treatment with both DMARDs and high dose corticosteroids. Corneoscleral tissue grafts developed favorably with infliximab.